Factor structure of the Positive and Negative Affect Schedule (PANAS) in adult women with fibromyalgia from Southern Spain: the al-Ándalus project - Fernando Estévez-López; Manuel Pulido-Martos; Christopher J. Armitage; Alison Wearden; Inmaculada C. Álvarez-Gallardo; Manuel Javier Arrayás-Grajera; María J. Girela-Rejón; Ana Carbonell-Baeza; Virginia A. Aparicio; Rinie Geenen; Manuel Delgado-Fernández; Víctor Segura-Jiménez (PeerJ, 2016)
Background: Fibromyalgia is a syndrome characterized by the presence of widespread chronic pain. People with fibromyalgia report lower levels of Positive Affect and higher levels of Negative Affect than non-fibromyalgia peers. The Positive and Negative Affect Schedule (PANAS)–a widely used questionnaire to assess two core domains of affect; namely ‘Positive Affect’ and ‘Negative Affect’ –has a controversial factor structure varying across studies. The internal structure of a measurement instrument has an impact on the meaning and validity of its score. Therefore, the aim of the present study was to assess the structural construct validity of the PANAS in adult women with fibromyalgia. Methods: This population-based cross-sectional study included 442 adult women with fibromyalgia (age: 51.3 ± 7.4 years old) from Andalusia (Southern Spain). Confirmatory factor analyses were conducted to test the factor structure of the PANAS. Results: A structure with two correlated factors (Positive Affect and Negative Affect) obtained the best fit; S-B χ2 = 288.49, df = 155, p < .001; RMSEA = .04; 90% CI of RMSEA = (.036, .052); the best fit SRMR = .05; CFI = .96; CAIC = −810.66, respectively. Conclusions: The present study demonstrates that both Positive Affect and Negative Affect are core dimensions of affect in adult women with fibromyalgia. A structure with two correlated factors of the PANAS emerged from our sample of women with fibromyalgia from Andalusia (Southern Spain). In this model, the amount of variance shared by Positive Affect and Negative Affect was small. Therefore, our findings support to use and interpret the Positive Affect and Negative Affect subscales of the PANAS as separate factors that are associated but distinctive as well.